-2(-6+6x)=-48

Simple and best practice solution for -2(-6+6x)=-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-6+6x)=-48 equation:



-2(-6+6x)=-48
We move all terms to the left:
-2(-6+6x)-(-48)=0
We add all the numbers together, and all the variables
-2(6x-6)-(-48)=0
We add all the numbers together, and all the variables
-2(6x-6)+48=0
We multiply parentheses
-12x+12+48=0
We add all the numbers together, and all the variables
-12x+60=0
We move all terms containing x to the left, all other terms to the right
-12x=-60
x=-60/-12
x=+5

See similar equations:

| -3(7-2x)=-33 | | 1/8(16k+8)=-5 | | 4x+8=58+3x | | 2x+5^(-x)=4 | | 7^3x=49^x-1 | | 0.5×x×x×x+3×x+8=0 | | n*8+3=26 | | 5(4x+8)-2(4-6x)=0 | | (1.2x+3.8)/4=(5.2x+1.8)/6 | | 40y-7=12y^2 | | -14=8-5x | | 5(3n-1)=55 | | 3(9+4x)=123 | | 2y-8=22-4y | | 2(7x-10)=36 | | 3x+2(x+7)=-11 | | 13×6=3x | | 38=4x+7x+5 | | (x-7/2)^2=0 | | -14-4x-3=3x-8-5x | | -x-3+7x=57 | | 6x+7=x+87 | | q(-4)+(1-q)(-4+5)=0 | | 1+8a=129 | | 1+8a=59 | | 3^4x+1=5 | | 8=10r+8-2r | | F=-6+2.5x | | X²-6x+20=0 | | 3(2x-4)=5x-(-3x+7) | | (x+9)2=121 | | 7y-2y-15=-5 |

Equations solver categories